A Novel Advances in Nano-Catalysis and its Impact on Sustainable Chemistry - S. J. Patil (International Journal of Scientific Research in Science and Technology, 2025)
Recent studies in nano-catalysis have shown that using nanomaterials to boost catalytic activity can lead to promising results in catalytic processes. To enhance catalytic performance, it is necessary to consider external stimuli. Using plasmatic nanoparticles for catalysis has shown that light-driven catalytic processes are possible. The nanomaterials part of the catalysis industry is moving towards catalysts that can do more than one thing and are easier to manage, more selective, and more efficient. This aligns with global objectives for more environmentally friendly and long-lasting chemical processes. Another area of research that scientists are interested in is the rational design of nanocatalysts. Researchers are combining computer modelling and machine learning techniques to achieve this goal successfully.
Keywords: Nano-catalysis; nanomaterials; sustainable chemistry; renewable energy